Philosophical Reflections: Critical Analysis of Learning Strategies for Science Practicum During the COVID-19 Pandemic - Budiyono Saputro; Muh Saerozi; Fadhil Ardhiansyah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The purpose of this study is to obtain a critical description of the learning strategy for science practicum during the COVID-19 pandemic. The research method was a qualitative descriptive study. The respondents of this study were lecturers and students of the Natural Sciences within the Indonesia Natural Sciences Tadris Association. The research instruments were in the form of questionnaires and a list of questions related to the learning of science practicum during the COVID-19 pandemic. The results showed the highest percentage of each learning strategy indicator for science practicum used by lecturers as follows: (1) 68.75% for the student center approach, (2) 50% for problem-based learning strategy, (3) 31.25% for self-practicum technique, (4) 31.25% for WhatsApp media, (5) 31.25% for self-assignment evaluation, (6) 93.75% for the indicator of the success of self-practicum, (7) 68.75% social media and signal supporting factors, (8) 31.25% for internet network obstacle, (9) 68.75% for the method to discover the practicum skills by playing the video of student’s results of practicum at home. The recommendation of this study should be carried out independently in each student's home by utilizing tools and materials around their environment and evaluation of learning is done through self-assignments or practicum videos sent to lecturers.